Tendencias de mortalidad y riesgo de muerte por cÃ¡ncer de hÃgado en MÃ©xico, 2000-2013 - Juan J. SÃ¡nchez-Barriga (Permanyer, 2021)
Introduction: Liver cancer (LC) is a public health problem in the world, since is the second leading cause of death and Mexico is no exception, in 2013 the LC ranked fourth of mortality among malignancies. Material and methods: The records of mortality associated to LC for the period 2000-2013 were obtained from National Institute of Statistics and Geography. National mortality rates were calculated by state and by socioeconomic region. The strength of association of the states of residency and educational level with mortality from LC was determined. Results: In 2000-2013, the crude death rate per 100,000 people increased from 4.2 to 4.9. Individuals with no schooling or incomplete elementary school the relative risk (RR) of dying from LC was the highest (RR 8.61, 95% CI 8.35-8.89), while in individuals with senior in high school or equivalent the RR decreased (RR 0.74, 95% CI 0.71-0.77). Chihuahua had the highest risk of dying [RR 30.3, 95% CI 19.6-46.8 (2000) and RR 22.3, 95% CI 15.1-33 (2013)]. Region 2 had the highest mortality rate. Conclusions: In Mexico in the study period, the crude death rate increased from LC. Individuals with no schooling or with incomplete elementary school the RR of dying from LC was the highest. Chihuahua had the highest mortality rate and the highest risk of dying. Region 2 had the highest mortality rate.